2022
DOI: 10.36660/abc.20210410
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude das Ondas F como Preditor de Tromboembolismo e de Sucesso da Cardioversão Elétrica em Pacientes com Fibrilação Atrial Persistente

Abstract: Fundamento: A fibrilação atrial (FA) é classificada, de acordo com a amplitude das ondas fibrilatórias (f), em ondas finas (FAf) e ondas grossas (FAg). Objetivos: Correlacionar a amplitude das ondas f com variáveis clínicas, laboratoriais, eletrocardiográficas e ecocardiográficas que indiquem alto risco de tromboembolismo e avaliar o seu impacto no sucesso da cardioversão elétrica (CVE). Métodos: Estudo retrospectivo, observacional, que incluiu 57 pacientes com FA não valvar persistente submetidos a CVE. A amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In prior reports it has been demonstrated that the coarse AF was associated with a higher success rate of cardioversion. [20][21][22] Of note, all these reports had short-to mid-term follow-up periods (up to 1 year), while we followed up patients with a median of 54 months, which may in part lead to different finding. Moreover, we showed that the thinner individuals were also associated with the presence of successful cardioversion.…”
Section: Discussionmentioning
confidence: 99%
“…In prior reports it has been demonstrated that the coarse AF was associated with a higher success rate of cardioversion. [20][21][22] Of note, all these reports had short-to mid-term follow-up periods (up to 1 year), while we followed up patients with a median of 54 months, which may in part lead to different finding. Moreover, we showed that the thinner individuals were also associated with the presence of successful cardioversion.…”
Section: Discussionmentioning
confidence: 99%